Intellectual Property Law in the Digital Economy Era: New Challenges and Countermeasures - Yao, Yongchen (International Journal of Global Economics and Management, 2024)
With the rapid development of the digital economy, intellectual property protection faces new challenges such as the definition and protection of data rights, the legal status of AI-generated works, cross-border infringement, the responsibility of internet platforms, and the protection of trade secrets. This paper analyzes the characteristics of the digital economy era and the specific issues faced by intellectual property law, proposing corresponding countermeasures. These include improving the data rights protection system, clarifying the legal status of AI-generated works, strengthening international cooperation, defining the responsibilities of internet platforms, and enhancing the protection of trade secrets. Through the integration of law and technology, international cooperation, and public education, the paper aims to promote the innovation and development of the intellectual property protection system to facilitate the healthy growth of the digital economy.